2022
DOI: 10.1101/2022.05.11.22274314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-ancestry genome-wide association study improves resolution of genes, pathways and pleiotropy for lung function and chronic obstructive pulmonary disease

Abstract: Lung function impairment underlies chronic obstructive pulmonary disease (COPD) and predicts mortality. In the largest multi-ancestry GWAS meta-analysis of lung function to date, comprising 580,869 participants, 1020 independent association signals identified 559 genes supported by ≥2 criteria from a systematic variant-to-gene mapping framework. These genes were enriched in 29 pathways. Individual variants showed heterogeneity across ancestries, age and smoking groups, and collectively as a genetic risk score … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Finally, we note that recently, a larger GWAS of lung function has been published; some of our novel findings are confirmed by examination in a larger sample size. For example, rs72703234 (near DMRT 2) did not meet replication criteria in Shrine et al [14], but was reported in 2022 [47].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that recently, a larger GWAS of lung function has been published; some of our novel findings are confirmed by examination in a larger sample size. For example, rs72703234 (near DMRT 2) did not meet replication criteria in Shrine et al [14], but was reported in 2022 [47].…”
Section: Discussionmentioning
confidence: 99%
“…We show contrasting patterns of phenotype association -for example highly specific associations for hypothyroidism (cAMP signalling) versus associations also with body composition, renal function and lipid traits (platelet activation pathways). As individuals may have high GRS for one or more pathways and low GRS for other pathways (17), individuals' pathway GRS profiles may relate to patterns of comorbidities, and could have implications for treatment choices in thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…First, Nick Shrine presented a multi-ancestry genome-wide association study (GWAS) of lung function, based on data arising from 49 different cohorts (n=580,869) including individuals with European, African, American, East, and South Asian ancestries [32]. By exploring multiple ancestries, Shrine et al identified over 1,000 independent signals for lung function, and proposed a novel multi-ancestry genetic risk score that is more predictive of lung function in diverse populations, compared to previous European ancestry genetic risk scores [33]. Second, Mohammad Talaei Pashiri presented an investigation of 55 lung development genes that aimed to explore shared development pathways explaining the association between lower lung function in adulthood and cardiovascular health, in the UK Biobank [34].…”
Section: Lung Function and Risk Factors Associated With Obstructive L...mentioning
confidence: 99%
“…By exploring multiple ancestries, S hrine et al . [ 33 ] identified >1000 independent signals for lung function and proposed a novel multi-ancestry genetic risk score that is more predictive of lung function in diverse populations compared to previous European ancestry genetic risk scores. Second, T alaei P ashiri et al [ 34 ] presented an investigation of 55 lung development genes that aimed to explore shared development pathways explaining the association between lower lung function in adulthood and cardiovascular health, in the UK Biobank.…”
Section: Lung Function and Risk Factors Associated With Obstructive L...mentioning
confidence: 99%